The Speech Act Associated with the Fundamental Kinship Relation in Karo Society - Barus, Efendi; Hasibuan, Ahmad Laut; Risnawaty, Risnawaty; Erwina, Emmy (International Journal of Educational Research Excellence (IJERE), 2024)
This research is intended to analyze about the speech act associated with the fundamental kinship relation in Karo society. The fundamental kinship relation in Karo society is concerned with the Metenget “alertful or paying great attention”, Metami “loving, giving soft words, flattery” and Mehamat “loyal, respectful, honour”. All of these three words must be expressed through words or speech. The method of research is done by using library research or by taking some references from the articles and books. The analysis of this research is found that the speech act which are divided into three, such as locutionary act, illocutionary act and perlocutionary act are utilized in the three fundamental kinship relations. It is not only in the party, but also every where while they are meeting together between anak beru “sisters or her husband”, senina “brothers or the same clan” and kalimbubu “mother’s brother and his wife”. The conclusion is that the types of the speech acts, such as locutionary act, illocutionary act and perlocutionary act are very important in the implementation of the three fundamental kinship relations like metenget, metami and mehamat.